BIBLICAL STUDIES AND THE ARMENIAN BIBLE, 1980-2002 - Cox, Claude E. (Revue biblique, 2005)
This article brings up to date an earlier article that appeared in RB 89 (1982), pp. 99-113, which surveyed the same subject for the period 1955-1980. It begins by listing five major symposia devoted to Armenian Bible and text preparation and then contains the following sections: 1. – Preparation of Editions of Biblical Texts; 2. – Patristics, divided into a) Works Written in Greek or Syriac and Translated into Armenian and, b) The Bible in Armenian Authors; 3. – Theology; 4. – Apocrypha and Pseudepigrapha; Conclusion, in which several deseridata are listed. In general the article reflects an active area of research, but where much remains to be done in the preparation of editions of texts to serve the larger field of Biblical studies. L'article complète et met à jour une parution précédente, dans RB 89 (1982), pp. 99-113, sur la période 1955-1980. Il commence par cinq symposiums consacrés à la bible arménienne. Ensuite : la préparation des éditions de textes bibliques ; la patristique (en grec ou syriaque, et traduite en arménien ; et chez les auteurs arméniens) ; la théologie ; et, enfin, les apocryphes et les pseudépigraphes. La conclusion présente des desiderata. L'ensemble illustre un domaine de recherche dynamique, mais où beaucoup reste à faire en matière de préparation d'édition de textes bibliques.